Interleukin 21 Controls mRNA and MicroRNA Expression in CD40-Activated Chronic Lymphocytic Leukemia Cells. - Loris De Cecco (PLoS ONE, 2015)
Several factors support CLL cell survival in the microenvironment. Under different experimental conditions, IL21 can either induce apoptosis or promote CLL cell survival. To investigate mechanisms involved in the effects of IL21, we studied the ability of IL21 to modulate gene and miRNA expressions in CD40-activated CLL cells. IL21 was a major regulator of chemokine production in CLL cells and it modulated the expression of genes involved in cell movement, metabolism, survival and apoptosis. In particular, IL21 down-regulated the expression of the chemokine genes CCL4, CCL3, CCL3L1, CCL17, and CCL2, while it up-regulated the Th1-related CXCL9 and CXCL10. In addition, IL21 down-regulated the expression of genes encoding signaling molecules, such as CD40, DDR1 and PIK3CD. IL21 modulated a similar set of genes in CLL and normal B-cells (e.g. chemokine genes), whereas other genes, including MYC, TNF, E2F1, EGR2 and GAS-6, were regulated only in CLL cells. An integrated analysis of the miRNome and gene expression indicated that several miRNAs were under IL21 control and these could, in turn, influence the expression of potential target genes. We focused on hsa-miR-663b predicted to down-regulate several relevant genes. Transfection of hsa-miR-663b or its specific antagonist showed that this miRNA regulated CCL17, DDR1, PIK3CD and CD40 gene expression. Our data indicated that IL21 modulates the expression of genes mediating the crosstalk between CLL cells and their microenvironment and miRNAs may take part in this process.